Optimal energy flow in integrated heat and electricity system considering multiple dynamics - Cai, Rong; Li, Yafei; Qian, Kejun (Frontiers in Energy Research, 2023)
Wide promotion of combined heat and power (CHP) units necessitates the combined operation of the power and heating system. However, the dynamics and nonlinearity in integrated heat and electricity systems (IHES) remain an obstacle to efficient and accurate analysis. To handle this issue, this paper constructs an optimal energy flow (OEF) model for the coordinated operation of the IHES considering the multiple dynamics. The dynamic heating system model is formulated as a set of nonlinear partial differential and algebraic equations (PDAE). The dynamic CHP model is formulated as a set of nonlinear differential and algebraic equations (DAEs). Then, the finite difference method (FDM) is adopted to make the dynamics tractable in the OEF. On this basis, a comprehensive OEF model for IHES is proposed. Simulations in two cases verify the effectiveness of the proposed method and highlight the significance of the dynamics in IHES.